POZNAŃ SCHOOL OF SOCIO-ECONOMIC GEOGRAPHY (AND SPATIAL MANAGEMENT) OF ADAM MICKIEWICZ UNIVERSITY (IN POZNAŃ) - Parysek, Jerzy J. (Quaestiones Geographicae, 2019)
This article presents the general characteristics of the Poznań school of socio-economic geography (and spatial management). Scientific school is usually understood as a community of scholars, representatives of a given scientific discipline, associated with a specific university (or universities) functioning in a given city, united by particular approaches to scientific problems and by accepted ideas, views, methods used etc., which has substantial achievements in a given scientific discipline. There is practically no scientific school without a master (or masters) who is an eminent scholar gathering a group of students and associates. The acknowledged output of this scholar – master, especially an innovative approach to solving research problems and also the influence of his/her scientific authority on students and associates, is usually an origin of a new scientific school. Professor Zbyszko Chojnicki, the founder of the Poznań school, was such a master. The article presents the creation of the School and its development, characterises the role of the Master, indicates the research approach and direction of the conducted studies he determined and discusses the scientific output of the Master and the three selected generations of students and, to a lesser extent, the auditing students. Emphasis is put on the achievements in the theory of geography and spatial management, methodology, paying particular attention to quantitative analysis methods and the innovative and original empirical research conducted as well as the significance of this output for Polish socio-economic geography and spatial management. What is also presented is the popularisation activity and the reflections on the future of the School. The article presents the author’s point of view.